A pitfall in hemoglobin A1c measurement with high performance liquid chromatography method in the diagnosis of onset of fulminant type 1 diabetes mellitus. Issue 11 (27th May 2022) - Oe, Yasuharu; Anno, Takatoshi; Katsuhara, Yukari; Sugahara, Ryo; Kobayashi, Miki; Yakusue, Mieko; Tamura, Masayo; Kimura, Yukiko; Kawasaki, Fumiko; Kaku, Kohei; Kaneto, Hideaki; Kitanaka, Akira
Abstract : We showed a case with the onset of fulminant type 1 diabetes mellitus (FT1DM) whose HbA1c could not be measured with HPLC method. We think that the reason why his HbA1c was not be detected was associated with the presence of labile hemoglobin A1c (LHbA1c). These result mean that it is possible that LHbA1c can bring about a pitfall on HPLC method in diagnosis of onset of FT1DM.